Variabilidade espacial de MO, P, K e CTC do solo sob diferentes usos e manejos - Cavalcante, Eloiza Gomes Silva [UNESP]; Alves, Marlene Cristina [UNESP]; Pereira, Gener Tadeu [UNESP]; Souza, Zigomar Menezes de (Universidade Federal de Santa Maria (UFSM), 2007)
O estudo da variabilidade espacial dos atributos químicos dos solos é particularmente importante em áreas onde o solo está submetido a diferentes manejos. O trabalho foi desenvolvido em Selvíria (MS), com o objetivo de avaliar a variabilidade espacial da matéria orgânica (MO), o fósforo (P), do potássio (K) e a capacidade de troca catiônica (CTC) em um Latossolo Vermelho distrófico sob diferentes usos e manejos. Os solos foram amostrados em uma malha, com intervalos regulares de 2m, perfazendo um total de 64 pontos, nas profundidades de 0,0-0,1m e 0,1-0,2m, nas seguintes áreas: vegetação natural (cerrado), plantio direto, plantio convencional e pastagem. O sistema de plantio direto apresentou acúmulo significativo de matéria orgânica, fósforo, potássio e elevação da CTC em relação aos demais sistemas estudados, além da melhoria nas condições químicas do solo. A matéria orgânica foi maior em relação ao sistema natural. As maiores variabilidades medidas por meio do coeficiente de variação foram observadas para o fósforo e o potássio, sendo que a matéria orgânica e a CTC apresentaram coeficiente de variação médio nos diferentes usos e manejos do solo.

The study of the spatial variability of the chemical attributes of the soils is particularly important in areas where the soil is submitted to different management. This work was developed in Selvíria (MS) with the objective of evaluating the spatial variability of the organic matter (MO), phosphorus (P), potassium (K) and cation exchange capacity (CEC) in a oxisol under different use and management conditions. The soils were collected in a grid, with regular intervals of 2m, total of 64 points, in the depths of 0,0-0,1m and 0,1-0,2m, in the use and management were: native vegetation (savannah), no-tillage, conventional system and pasture. The system of no-tillage presented significant accumulation of organic matter, phosphorus, potassium and elevation of CEC in relation to the other studied systems, besides the improvement in the chemical conditions of the soil, the organic matter was larger in relation to the natural system. The largest variabilities measured through the variation coefficient, they were observed for the phosphorus and potassium, and the organic matter and CEC presented medium variation coefficient in the different uses and management of the soil.
Spatial variability of MO, P, K and CTC of soil under different use and management conditions
Keywords: chemical attributes of soil; soil tillage; Geostatistics; Oxisol; atributos químicos do solo; preparo do solo; Geoestatística; Latossolo